Printed Editions of Ratio breuis et expedita conscribendi genera epistolarum illustriora, Attributed to the Humanist Petrus Ioannes Nunnesius (Minerva, 2017)
This paper compares and analyzes three different editions of Ratio breuis et expedita conscribendi genera epistolarum illustriora, attributed to the Spanish humanist Petrus Ioannes Nunnesius († 1602). The aim of the paper is to assess its importance for the textual tradition of De conscribendis epistolis, a treatise of greater length composed by the aforementioned author.
Keywords: renaissance epistolography; Petrus Ioannes Nunnesius; ratio breuis